PLURALISM RECONSTRUCTION IN FIQH STUDIES - Kusnan, Kusnan (The Islamic Education and Multiculturalism Foundation, 2020)
Abstract: Pluralism in religious studies is often placed in context and theological significance. As a result of this understanding, the understanding of the theological concepts in all religions led to the prohibition by MUI. While in some circles it provides an understanding of pluralism, in a religious context, from the point of view of its social function, which is a system of life that binds people in units or social groups. Pluralism is not an understanding that says all religions are the same. Pluralism must be separated from relativism and syncretism. In order to lead to a practical order in pluralist social fiqh, courage is required in deconstructing fiqh openly. In the fiqh of pluralism the construction that must be built is to understand plurality as a fact of sausageal where, each individual and group to know and understand each other. So it is necessary to restore universal values such as common benefit, egaliterianism, rationalism, pluralism as the principles of paradigmatic fiqh so as not to get caught up in the wedges of litreralism, fundamentalism, authoritarianism and conservatism